Poverty in Britain in 1904: an early social survey rediscovered - Ian Gazeley; Andrew Newell (Institute for the Study of Labor (IZA), 2007)
Until now there have been no national estimates of the extent of poverty in Britain at the turn of the 20th century. This paper introduces a newly-discovered household budget data set for the early 1900s. These data are more representative of urban working households in Britain in the period than any other existing record, although they are not without deficiencies. We use these data to estimate urban poverty in the British Isles in 1904. Applying Bowley's poverty line we find that about fifteen percent of people in urban working class households had income insufficient to meet minimum needs. This is close to Rowntree's estimate of primary poverty for York 1899 and in the range that Bowley found in Northern towns in 1912-3. This average masks a heavy concentration of poverty among the unskilled and those with large families.
Keywords: 330; Poverty; Britain; 1904; Armut; Städtische Armut; Arbeiterklasse; Haushaltsbudget-Statistik; Großbritannien